Autism and dual immersion: sorting through the questions. Issue 4 (6th September 2018) - Baker, Diana; Roberson, Audrey; Kim, Hyejung
Abstract : Purpose: The dual immersion (DI) model of bilingual education, which focuses on educating language-minority and majority students side by side using the two languages in roughly equal proportions, is gaining popularity. And yet, students with disabilities – even those who are already multilingual – are routinely steered away from such programs in favor of English-only special education options. The paper aims to discuss these issues. Design/methodology/approach: This paper explores the potential benefits and challenges associated with including multilingual students with autism in DI classrooms, beginning with an exploration of literature related to students with autism who are also multilingual learners (MLLs) (irrespective of educational placement), followed by a small body of literature on the inclusion of students with disabilities in general in DI programs, and finally an analysis of the characteristics of DI classrooms to extrapolate about the ways in which this environment might be both supportive of and challenging for students with autism. Findings: The analysis reveals that DI programs are simultaneously well positioned (theoretically) and ill equipped (practically) to effectively support MLLs who are also on the autism spectrum. Originality/value: In spite of mounting evidence that being multilingual may advantage children with autism, very little scholarship has even raised the question of whether students with autism might benefit from participation in bilingual programs where academic instruction is delivered in two languages (Beauchamp and MacLeod, 2017 ; Durán et al., 2016 ; Marinova-Todd et al., 2016 ; Seung et al., 2006 ). This paper identifies practical implications related to including students with autism in DI programs and suggests directions for future research.